PENGEMBANGAN BAHAN AJAR PENDIDIKAN PANCASILA BERBASIS MULTIMEDIA DENGAN MENGGUNAKAN APLIKASI SPARKOL VIDEOSCRIBE - Untung Joko Basuki; Muhammad Sholeh (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Innovation in learning must follow the development of technology. Pancasila education as a basic course that must be taken by students in a package with teaching materials that are not only text based but also involving multimedia such as pictures, animation, sound or other media. In this study, teaching materials Pancasila Education with multimedia are developed by using video scribe application. By using Video Scribe this process of making teaching materials can be conducted easily without any programming process. The material developed refers to Pancasila education books for higher education published by the Directorate General of Learning and Student Affairs, Ministry of Research and Technology of DIKTI. The method used is ADDIE method that consists of Analysis, Design, Development, Implementation and Evaluation